Formulation of Microbial Inoculants by Encapsulation in Natural Polysaccharides: Focus on Beneficial Properties of Carrier Additives and Derivatives - Vassilev, Nikolay; Vassileva, Maria; Martos, Vanessa; Garcia del Moral, Luis F.; Kowalska, Jolanta; Tylkowski, Bartosz; Malusá, Eligio (Frontiers in Plant Science, 2020)
In the last 10-15 years, the wide application of bioformulated plant beneficial microorganisms is accepted as an effective alternative of chemical agro-products. Two main problems can be distinguished in their production and application: a) economical competiveness based on the overall up-stream and down-stream operational costs, and b) development of commercial products with a high soil-plant colonization potential in controlled conditions but not able to effectively mobilize soil nutrients and/or combat plant pathogens in the field. To solve the above problems, microbe-based formulations produced by immobilization methods are gaining attention as they demonstrate a large number of advantages compared to other solid and liquid formulations. This mini-review summarizes the knowledge of additional compounds that form part of the bioformulations. The additives can exert economical, price-decreasing effects as bulking agents or direct effects improving microbial survival during storage and after introduction into soil with simultaneous beneficial effects on soil and plants. In some studies, combinations of additives are used with a complex impact, which improves the overall characteristics of the final products. Special attention is paid to polysaccharide carriers and their derivates, which play stimulatory role on plants but are less studied. The mini-review also focuses on the potential difficulty in evaluating the effects of complex bio-formulations.